Information on the principal events which took place in the Government of Spain, from the commencement of the insurrection, in 1808, to the dissolution of the ordinary cortes, in 1814 . [...]. Transl. from the original Spanish by W. Walton.; (London, 1820)
Pamphleteer, 17 (1820), 23.